Strategi Wisata Edukasi Kampung Lele Dalam Persaingan Industri Wisata Halal Kediri (Tinjauan Porter Five Force dan Pondasi Rancang Bangun Ekonomi Islam) - Andriani (Al-Muraqabah: Journal of Management and Sharia Business, 2023)
Competition in the halal tourism industry in Indonesia is currently busy. The needs of the Muslim community in the halal industry, recreational areas include aspects that must be considered. In addition to meeting the needs of the Muslim community, halal tourism also encourages economic growth. An effective competitive strategy will create the advantages of a tourist spot with its competitors. This study aims to examine the competitive strategies carried out by a tour in Kediri Regency which is developing quite well including during the pandemic. Tourism in Kediri has several strategies in competing with fellow tourism industries. So it is very relevant when reviewed in the Porter Five Force Approach which is a method of strength in competition among industries. In addition, as a form of competition in the halal industry, the basic values of Islamic economics become the foundation of Islamic economic design to become the basis for the economic and business activities of Muslim communities. The results of this study explain that the competitive strategy of Wisata Edukasi Kampung Lele Kediri through the Porter Five Force approach has realized five aspects of strength which include strategies to face new competitors, strategies to face substitute products, bargaining power strategies for buyers, bargaining power strategies for suppliers, and facing similar industry competition. Based on the design foundation, the basic values of Islamic economics such as tawhid, adl', nubuwwah, khilafah, and ma'ad have been well realized by Wisata Edukasi Kampung Lele Kediri.